A prospective comparison of times to presentation and treatment of regional and remote head and neck patients in North Queensland, Australia. Issue 8 (August 2016) - Tan, J. Y.‐A.; Otty, Z. A.; Vangaveti, V. N.; Buttner, P.; Varma, S. C.; Joshi, A. J.; Kelly, J.; Collins, M.; Sabesan, S. S.
Abstract : Background/Aim: This study aims to examine differences between outer regional (OR) and remote/very remote (RVR) patients in northern Queensland, Australia in the times taken to receive various aspects of head and neck cancer management. Methods: Our study prospectively recruited head and neck cancer patients presenting to three North Queensland regional hospitals from January 2009 to January 2011. Data on demographic and cancer‐specific details, comorbidities and timing of presentation to various services, were collected using a self‐administered questionnaire that included two questions in relation to possible reason for delays to health services. Multivariate linear regression analyses were conducted to assess the effects of various demographic characteristics on time delays. Survival and disease recurrence data were analysed in 2014. Results: One hundred and fifty‐eight patients participated. RVR patients had significantly longer median times between diagnosis and first treatment compared with OR patients ( P = 0.015). Indigenous patients had significant delays from diagnosis to first treatment ( P = 0.013) and visit to first specialist and treatment ( P = 0.031) compared to non‐Indigenous patients. Longer median times between symptoms and first treatment was associated with low income ( P = 0.03) and lower education level ( P = 0.04). Disease recurrence was higher for RVR patients compared with OR patients ( P = 0.04), without significant differences in overall survival. Possible reasons for delays included patient and professional factors. Conclusion: Significant delays in various aspects of head and neck cancer management were associated with remoteness, Indigenous and socioeconomic status. While patient and professional factors could be addressed at local levels, sustainable improvement in outcomes requires a state and national level approach.